Altered muscle activation following hamstring injuries. Issue 2 (10th March 2011) - Sole, Gisela; Milosavljevic, Stephan; Nicholson, Helen; Sullivan, S John
Abstract : Objective: The purpose of this study was to compare the electromyographic (EMG) activity of gluteal and thigh muscles of sportspeople with a recent hamstring injury with uninjured controls during a weight-bearing task. Study design: Cross-sectional. Setting: University laboratory. Participants: 16 participants with a hamstring injury (hamstring-injured group, HG) and 18 control participants (control group (CG)) participated in the study. Main outcome measure: The EMG activity of gluteal, quadriceps and hamstring muscles was recorded during a movement from double- to single-leg movement using surface electrodes. Results: The EMG onsets of biceps femoris and medial hamstrings were significantly earlier for the HG injured and the uninjured sides in preparation for single-leg standing when compared with the CG average. There were no differences in onsets for the gluteal and quadriceps muscles when comparing the injured or uninjured legs of the HG to the bilateral average of the CG. Conclusion: The earlier onset of the injured and the uninjured hamstrings in preparation for single leg stance of the HG in comparison with the CG suggests an alteration in the motor control of these muscles. Altered neuromuscular control following a hamstring injury may be a factor to be considered in the rehabilitation of hamstring injuries.